Water-soluble magnetic-carbon nanotubes nanocomposites for efficient adsorption of Cu(II) from aqueous solution. Issue 4 (2nd April 2016) - Zhang, Liyuan; Tai, Yanfang; Lv, Changpeng; Wang, Chuanhu
ABSTRACT: In this study, the water-soluble magnetic-multi-walled carbon nanotubes nanocomposites were fabricated via a facile and efficient approach and were characterized by X-ray diffraction, energy-dispersive X-ray, and transmission electron microscopy in detail. The nanocomposites could be employed as an effective adsorbent for removal of heavy metal ions, Cu(II) ions, from aqueous solution. It is noteworthy that the novel adsorbent displayed good water-dispersibility, rapid absorption rate, high absorption capacity, and convenient magnetic separation. Furthermore, the nanocomposites could be recovered and recycled for 10 consecutive trials without significant loss of its activity.